Role of Tryptophan in Microbiota-Induced Depressive-Like Behavior: Evidence From Tryptophan Depletion Study - Lukić, Iva; Getselter, Dmitriy; Koren, Omry; Elliott, Evan (Frontiers in Behavioral Neuroscience, 2019)
During the past decade, there has been a substantial rise in the knowledge about the effects of gut microbiota on host physiology and behavior, including depressive behavior. Initial studies determined that gut microbiota can regulate host tryptophan levels, which is a main serotonin precursor. A dysfunctional serotonergic system is considered to be one of the main factors contributing to the development of depression. Therefore, we hypothesized that regulation of brain tryptophan and serotonin can explain, at least partly, the effects of microbiota on depressive behavior. To test this hypothesis, we examined depressive-like behavior and brain levels of serotonin and tryptophan, of germ free (GF) and specific-pathogen free (SPF) mice under basal conditions, or after acute tryptophan depletion (ATD) procedure, which is a method to decrease tryptophan and serotonin levels in the brain. In basal conditions, GF mice exhibited less depressive-like behavior in sucrose preference, tail-suspension and forced swim tests, compared to SPF mice. In addition, in mice that were not subjected to ATD, GF mice displayed higher levels of tryptophan, serotonin and 5-hydroxyindoleacetic acid (the main degradation product of serotonin) in medial prefrontal cortex (mPFC) and hippocampus (HIPPO), compared to SPF mice. Interestingly, ATD increased depressive-like behavior of GF, but not of SPF mice. These behavioral changes were accompanied by a stronger reduction of tryptophan, serotonin and 5-hydroxyindoleacetic acid in mPFC and HIPPO in GF mice after ATD, when compared to SPF mice. Therefore, the serotonergic system of GF mice is more vulnerable to the acute challenge of tryptophan reduction, and GF mice after tryptophan reduction behave more similarly to SPF mice. These data provide functional evidence that microbiota affects depression-like behavior through influencing brain tryptophan accessibility and the serotonergic system.